PERSEPSI AKUNTAN PUBLIK, AKUNTAN PENDIDIK DAN MAHASISWA AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA - Ummy Sholihah; Nur Diana; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
AbstractThe purpose of this study is to determine whether there is a distinctionbetween accountants educators, public accountants and accountants student toethical codes Indonesian Accountants Association (IAI). Sampling in this researchis by using purposive sampling with criteria including: (1) accountant educatorshave the profession of teaching staff (lecturers) high educated Malang IslamicUniversity and the State University of Malang, (2) auditors working as partners /associates, managers, auditors senior, junior auditors and the staff in the office ofthe Public Accountant in Malang, (3) students S1 the Islamic University ofMalang, in the study are students who have taken auditing. Ethical Principlesconsists of elements that eight: responsibilities of the profession, the publicinterest, integrity, objectivity, competence and prudence, confidentiality,professional behavior, technical standards. This study uses primary data wherethe data was collected through questionnaires deployment to several publicaccounting firm, Faculty of Economics, Malang Islamic University, andUniversity of Malang in Malang. In this study, the population is a publicaccountant, accountant educator, and student accounting. It can be concludedthat of the eight ethical principles of the three variables show that there aredistinction in perception between educators accountants, public accountants andaccountants student to ethical codes Indonesian Accountants Association (IAI).Factor knowledge. Keywords: Perception, accounting educators, public accountants and accountingstudents.